2009
DOI: 10.2304/elea.2009.6.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Identity in Youth Media Arts Organizations: A Comparative Case Study

Abstract: In this article the authors explore the relationship between concepts of identity and the purpose, process, and products of youth media arts organizations. Since the explicit mission of these organizations is to work with adolescents to explore and represent identities, the authors develop our understanding of how organizations conceptualize identity development and how these concepts shape the digital film-making process and products. In a comparative case study of In Progress (St Paul, Minnesota) and Reel Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Because of the focus on composition, makerspaces offer a place for participants to create and recreate their identities alongside their compositions. Halverson, Lowenhaupt, Gibbons, and Bass (2009) found that participants experimented with different ways of being because there were limited social consequences in makerspaces. Therefore, makerspaces can provide a space for students to evaluate their current ideations in a nonthreatening, creative environment.…”
Section: Constructing a New Identitymentioning
confidence: 99%
“…Because of the focus on composition, makerspaces offer a place for participants to create and recreate their identities alongside their compositions. Halverson, Lowenhaupt, Gibbons, and Bass (2009) found that participants experimented with different ways of being because there were limited social consequences in makerspaces. Therefore, makerspaces can provide a space for students to evaluate their current ideations in a nonthreatening, creative environment.…”
Section: Constructing a New Identitymentioning
confidence: 99%
“…Ainsi, elle est à la fois l'objet et l'approche pour comprendre l'identité. Une interrelation intime réside entre la narration et l'identité (Ricoeur 1990) et celle-ci peut s'intensifier durant l'adolescence (Halverson et al 2009). Cette période de transition identitaire peut être positivement alimentée par différents procédés narratifs.…”
Section: La Narration Et La Multimodalitéunclassified
“…While the literature chronicling new college students' participation in digital media literacy and production activities is sparse, the literature on out-of-school media production organizations who work with adolescents aged 14-20 shows the value of these opportunities for empowering young people through digital media literacy (Halverson & Gibbons, 2010;Halverson et al, 2009;Hull & Katz, 2006;Nelson, Hull, & Roche-Smith, 2008;Soep, 2006). While the literature chronicling new college students' participation in digital media literacy and production activities is sparse, the literature on out-of-school media production organizations who work with adolescents aged 14-20 shows the value of these opportunities for empowering young people through digital media literacy (Halverson & Gibbons, 2010;Halverson et al, 2009;Hull & Katz, 2006;Nelson, Hull, & Roche-Smith, 2008;Soep, 2006).…”
Section: Digital Media Production and Identitymentioning
confidence: 99%
“…Specifically, producing autobiographical art supports adolescents in exploring possible selves and in affiliating with traditional stigmatized identities in adaptive ways (Halverson, 2009). Furthermore, artistic production processes support both individualistic and collectivistic conceptions of identity, opening up the possibility that multiple models for development can be accommodated within the same type of instructional setting (Doerr-Stevens, 2011;Halverson, Lowenhaupt, Gibbons, & Bass, 2009), an important feature for learning environments that hope to include students from a variety of home communities and to facilitate positive developmental trajectories.…”
Section: Introductionmentioning
confidence: 99%